FORMULATING A MODERN SERVICE DELIVERY STRATEGY IN THE ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS (International Congress on Economics, Management and Business Studies, 2026)
This research abstract analyzes the theoretical and practical aspects of formulating modern service delivery strategies within higher education institutions. The competitiveness of a modern higher education institution depends not only on the content of educational programs and faculty expertise but also on the quality and accessibility of academic, administrative, informational, career, and digital services provided to students. In service marketing theory, a deep understanding of consumer needs and the continuous improvement of service quality are regarded as crucial factors for an organization’s sustainable development. From this perspective, student-centered management, digitalization, feedback mechanisms, the implementation of service standards, and the monitoring of quality indicators are identified as key components of a modern strategy in higher education. The study outlines the stages of formulating a service delivery strategy and develops practical recommendations for its enhancement.
Keywords: higher education, educational services, service delivery strategy, student-centered approach, digitalization, quality of education, service quality, innovation, competitiveness, electronic services, feedback.